Intercultural perceptions among undergraduate students in English for Business and Economics courses. - NTELIOU, ELEFTHERIA; KEHAGIA, OLGA (International Journal of Language, Translation and Intercultural Communication, 2016)
The practice of intercultural communication should be a primary goal of Language for Specific Purposes (LSP) courses in tertiary education, because, through language instruction, future professionals can become aware of intercultural differences and develop strategies to deal with them, thus equipping themselves with necessary skills for effective cross-cultural communication in a globalized work environment. In this study, the intercultural awareness of first and second year undergraduate students attending an English for Business and Economics course was examined in relation to their interest in the economy and culture of other countries as well as to their preferred sources of information about current economic issues. Their preferences and perceptions regarding the intercultural elements incorporated in the methods and material used in the English course were also explored. The analysis of the Likert-type questionnaire revealed that intercultural awareness needs to be further practiced in class and led to important implications for the teaching methods and tasks used in the LSP courses.